A Ordem do Templo em Portugal : algumas considerações em torno das fontes para o seu estudo - Fernandes, Maria Cristina Ribeiro de Sousa (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
With this study, we intend to call attention to the problem of the sources concerning the Order of the Temple. The absence of a separate register office, the dispersion provoked by the process of extinction and its international dimension are aspects which make their identification more difficult, given that these sources are scattered and are often mistaken for the documentation of the Order of Christ, the preferential heir of its patrimony.